2020
DOI: 10.1186/s12935-020-01618-9
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of protein regulator of cytokinesis 1 facilitates tumor growth and indicates unfavorable prognosis of patients with colon cancer

Abstract: Background Protein regulator of cytokinesis 1 (PRC1) has been reported to play important role in the pathogenesis of various cancers. However, its role in colon cancer has not been studied. Here, we aimed to investigate the biological functions and potential mechanism of PRC1 in colon cancer. Methods The expression level of PRC1 in colon cancer tissues and cell lines was detected by quantitative real-time polymerase chain reaction (qRT-PCR), Western blotting, and immunohistochemical (IHC) staining of a tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Jia et al con rmed that PRC1 is highly expressed in bladder cancer, and They reported that miR-139-5p derived from exosomes (hUCMSCs) could upstream regulate PRC1 expression, thereby affecting tumor invasion and metastasis 23 . Furthermore, it also has been reported that PRC1 could accelerates cell cycle, inhibits tumor cell apoptosis, and correlates with poor prognosis in Colon cancer 24 . As for ovarian cancer, Bu et al reported that forkhead box protein M1 (FOXM1) can regulated the mRNA and protein expression of PRC1, they found that PRC1 is highly expressed in ovarian cancer and is associated with sensitivity to platinumbased chemotherapy, which predicts poor prognosis 25 .…”
Section: Discussionmentioning
confidence: 94%
“…Jia et al con rmed that PRC1 is highly expressed in bladder cancer, and They reported that miR-139-5p derived from exosomes (hUCMSCs) could upstream regulate PRC1 expression, thereby affecting tumor invasion and metastasis 23 . Furthermore, it also has been reported that PRC1 could accelerates cell cycle, inhibits tumor cell apoptosis, and correlates with poor prognosis in Colon cancer 24 . As for ovarian cancer, Bu et al reported that forkhead box protein M1 (FOXM1) can regulated the mRNA and protein expression of PRC1, they found that PRC1 is highly expressed in ovarian cancer and is associated with sensitivity to platinumbased chemotherapy, which predicts poor prognosis 25 .…”
Section: Discussionmentioning
confidence: 94%
“…Protein regulator of cytokinesis 1 (PRC1), localized on chromosome 15q26.1, is strongly related to cell movement and mitosis 27 . Current studies have also shown that PRC1 is up‐regulated in various tumors such as ovarian cancer, esophageal cancer and colon cancer, and exerts pro‐cancer effect 28–30 . As for HCC, Chen et al identified that PRC1 could promote HCC metastasis and recurrence 31 .…”
Section: Discussionmentioning
confidence: 99%
“…27 Current studies have also shown that PRC1 is up-regulated in various tumors such as ovarian cancer, esophageal cancer and colon cancer, and exerts pro-cancer effect. [28][29][30] As for HCC, Chen et al identified that PRC1 could promote HCC metastasis and recurrence. 31 In our…”
Section: Discussionmentioning
confidence: 99%
“…We further searched the literature in PubMed for associations among the 10 hub genes in CRC. Recent studies revealed that upregulated CDK1 promotes CRC cell proliferation via the inhibition of the p53 pathway ( Gan et al, 2017 ), CCNB1 overexpression exerts oncogenic role in CRC cells by phosphorylating CDK1 ( Fang et al, 2014 ), high expression of MAD2L1 drives aneuploidy and carcinogenesis in CRC ( Ding et al, 2020 ), TPX2 promotes proliferation and tumorigenicity of colon cancer cells ( Wei et al, 2013 ), MELK overexpression is significantly correlated with advanced tumor stage and further lymph node metastasis ( Gong et al, 2018 ), TRIP13 and KIF4Acould promote CRC cell proliferation, invasion and migration and subcutaneous tumor formation ( Hou et al, 2018 ; Sheng et al, 2018 ), overexpression of PRC1 and ANLN facilitate CRC tumor growth and proliferation ( Wang et al, 2016 ; Xu et al, 2020 ). The increase expression of these hub genes is closely related to the occurrence and development of CRC.…”
Section: Discussionmentioning
confidence: 99%